Pengaruh Kemudahan, Manfaat, Dan Risiko Terhadap Kepuasan Penggunaan Qris Pada Mitra UMKM Bank BSI KCP Citeureup 3 - A Muiz Ubaidillah; A Mulyadi Kosim; Nurman Hakim (CV. ITTC INDONESIA, 2025)
The development of digital technology has driven transformation in the financial sector, especially in non-cash payment systems such as QRIS (Quick Response Code Indonesian Standard). This study aims to analyze the effect of convenience, benefits, and risks on satisfaction with QRIS use on MSME partners of Bank Syariah Indonesia (BSI) KCP Citeureup3, Bogor Regency. The background of this study is based on the increasing use of digital financial services in Indonesia, but several problems are still encountered, such as the low position of BSI QRIS in terms of usage and user concerns about system security and reliability. The research method used is quantitative, with respondents being MSME actors who use QRIS from BSI as a payment method. The results of this study are expected to contribute to the development of literature, implementation of Islamic banking policies, and be a reference for BSI in improving QRIS services to MSME partners. This study also provides an overview of how perceptions of convenience, benefits, and risks affect the level of user satisfaction in utilizing digital payment services.